(a+b).(a-b) para a:-4 e b:-1/2
Soluções para a tarefa
Respondido por
0
(a+b)x(a-b)= (-4+(-1/2))x(-4-(-1/2)) (tira o mmc)
(a+b)x(a-b)= (-8-1/2) x (-8+1/2)
(a+b)x(a-b)= (-9/2)x (-7/2)
(a+b)x(a-b)= 63/4 ou 15,75
(a+b)x(a-b)= (-8-1/2) x (-8+1/2)
(a+b)x(a-b)= (-9/2)x (-7/2)
(a+b)x(a-b)= 63/4 ou 15,75
Respondido por
0
Basta substituir ...
(a+b).(a-b)
(-4+(-1/2)).(-4-(-1/2))
(-4-1/2).(-4+1/2)
(-8/2-1/2).(-8/2+1/2)
(-9/2).(-7/2) = 63/4 ou 15,75. ok
(a+b).(a-b)
(-4+(-1/2)).(-4-(-1/2))
(-4-1/2).(-4+1/2)
(-8/2-1/2).(-8/2+1/2)
(-9/2).(-7/2) = 63/4 ou 15,75. ok
Perguntas interessantes
Biologia,
11 meses atrás
Geografia,
11 meses atrás
Português,
11 meses atrás
Contabilidade,
1 ano atrás
Sociologia,
1 ano atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás